The Individual vs. Society in Rabbi Shlomo Zalman Auerbach’s Halakhic Rulings - Mashiach, Amir (The review of rabbinic Judaism, 2017)
Rosh Yeshivat Kol Torah in Jerusalem for more than forty years, Rabbi Shlomo Zalman Auerbach was one of the most influential Halakhic decisors of the twentieth century. Rabbi Auerbach was a major figure in Haredi society which makes his Halakhic involvement in military issues more interesting. An examination of his Halakhic rulings in this matter shows that Rabbi Auerbach comprehended not only the complexity of being a religious soldier in the Army but also the complexity of the operational needs of the Army. Here I identify and analyze Rabbi Auerbach’s Halakhic rulings on military issues in two aspects: a) regular military issues; b) different Halakhic issues on which Rabbi Auerbach imported military discussions and terminology into the halakhic discourse. Moreover, I show that Rabbi Auerbach worked in the light of the principle, “The Nullification of the Individual” (my terminology). Finally, I compare Rabbi Auerbach’s attitude towards Citizen-State issues to that of the German philosopher G.W.F. Hegel.